A Boundary-Value Problem for Normalized Finsler infinity-Laplacian Equations with Singular nonhomogeneous terms. (January 2020) - Biset, Tesfa; Mebrate, Benyam; Mohammed, Ahmed
Abstract: We study boundary-value problems of Finsler infinity-Laplacian equations with nonhomogeneous terms that may exhibit singularity when solutions vanish on the boundary.